Making the social world : the structure of human civilization - Searle, John R. (Oxford University Press, 2010)
"John Searle offers a profound understanding of how we create a social reality - a reality of money, property, governments, marriages, stock markets, and cocktail parties. The paradox he addresses in Making the Social World is that these facts exist only because we think they exist, and yet they have an objective existence." "Continuing a line of investigation begun in his earlier book The Construction of Social Reality, Searle identifies the precise role of language in the creation of all "institutional facts." His aim is to show how mind, language, and civilization are natural products of the basic facts of the physical world described by physics, chemistry, and biology. Searle explains how a single linguistic operation, repeated over and over, is used to create and maintain the elaborate structures of human social institutions."--BOOK JACKET.